E-government implementation in Region V SUCs - Rubio, Gerry S. (The Philippine Journal of Development Communication, 2009)
A survey was conducted among 16 key informants from eight state colleges and universities (SUCs) in Region V from May 8-18, 2007 to determine their implementation of the E-Commerce Law (RA 87977) and the constraints to their compliance. Specifically, the research (1) determined the SUCs' information and communication technology (ICT) capabilities and resources in building, improving, and maintaining their websites; (2) assessed their level of awareness on basic provisions regarding e-governance; and (3) identified their constraints in ICT management and administration. The fourth objective categorized the websites of SUCs downloadable as of March 2008 according to the standards of the United Nations and the American Society of Public Administration (UN-ASPA) Five Stages of E-Government. Finally, recommendations are forwarded to improve the implementation of the e-governance among the SUCs.